Holistic approach in cholera outbreak: the Petaling experience - Rushidi R.,; Rozanim K.,; Syarifa E.W.P.,; Aniza I.,; Enna H.,; Husnina I., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2002)
A cholera outbreak reported at the end of June 2001, from the Midlands Estate Petaling gave rise to three (3) cases and fifteen (15) carriers identified. An investigation was conducted to understand the epidemiological characteristic, identify the source of the outbreak and effective control measures. Upon notification, quick and prompt actions were taken including active case detection. Nine hundred and fifty (950) contacts of the whole estate and neighbouring population and one hundred and forty-four (144) food handlers were examined and rectal swabs were taken. Daily morbidity data were colleted and recorded for analysis. Disinfections spraying, inspection of drinking water supply, sewage disposal and vector survey was done. Twenty-two (22) and thirty-seven (37) water and food samples respectively together with twelve (12) environmental swabs were taken for Vibrio cholarae analysis. To control the outbreak comprehensively, several relevant agencies were consulted to participate actively as one team in combating the outbreak. The Selangor State Exco and the Head of State were also very committed in tackling the disease. Shah Alam City Council, Indah Water Consortium, Selangor State Economic Development Coporation, Selangor Water Department, and Alam Flora were directed to act swiftly with Selangor State Health Department and Petaling District Health Office to upgrade the infrastructure facilities and the sanitary hygiene in that area. Potable water supply, proper disposal of waste and sewage system were temporarily installed. The residents were also promised by the authorities to be shifted to nearby low- cost housing scheme in a month’s time. Concurrently, activities on active case detection and a health education programmed are continuously conducted to ensure that the outbreak is being contained. Lectures, dialogues session, counseling and distribution of health education materials were carried out to ensure that the people understand the disease. During this one-week outbreak, three (3) cases and fifteen (15) carriers were identified. The fifteen (15) carriers were identified through active case detection. Both cases and carriers were that of Vibrio cholarae serotype Ogawa. No death was reported. A total of thirty-three (33) food premises were closed under the Communicable Disease Control Act 1988. The environmental swab taken from the rubber band covering a leakage from the main pipe was positive for Vibrio cholarae. This pipe supplies the drinking water to the residents in the estate. This outbreak was primarily due to poor and inadequate infrastructure that led to cross contamination between the drinking water and the sewage system. Effective and comprehensive preventive and control measures was taken to contain this outbreak within the estate, implicating the importance of thorough investigation and active case detection together with the sustainable networking and commitment between the various agencies.